Molecole d'autore in cerca di memoria Dramma scientifico-civile in due atti - Dei, Luigi (Firenze University Press, 2011)
Based loosely on Primo Levi's Il Sistema Periodico, the play is set in a Fahrenheit 451 scenario. In this world without either books or memory, a man of the street arrives with a bundle of not easily decipherable papers: with the help of the narrative voice, of his friends - Science, Technology and Nature - and of two actors at length off-stage, Primo and his friend Alberto, the man succeeds in reconstructing the episode of the story Cerio. Through memory he thus reconstructs the lost identity, that is our history. Science, Technology and Nature allow the man without memory to master scientific knowledge and free himself from his state. The drama finds its catharsis in a poignant passage, inspired by the story Carbonio, which lyrically sets up a temporal link between an atom of carbon from the smoke of a crematorium and the same dwelling within the body of each one of us: a poetic parabola of a science immersed in the life and history of man.